Advances in Higher Education - Lloret Mauri, Jaime (UPV[Scientia], 2016)
Higher education institutions play an important role as leaders in knowledge creation and dissemination by setting the grounds for society to advance and to improve welfare.Despite the long-standing tradition of some higher education systems, Higher Education continuously evolves to adapt to the challenges that current societies open up to.The objective of this book is to capture some recent advances made in Higher Education by addressing these challenges.The book is arranged in five parts in accordance with these topics.Part I is related to the most important input of higher education institutions.The next three parts of the book analyses different aspects of the learning process that take place in Higher Education. Part II assesses student learning from different points of view.Part III contains two chapters on the creation and availability of resources in higher education institutions.Part IV describes and analyses some innovative teaching and learning methods. Finally, Part V consists of three chapters that deal with the relation of Higher Education with industry, which is the main destination of graduates